Strategi Bertahan Hidup Petani Karet di Desa Geringging Jaya Kecamatan Sentajo Raya Kabupaten Kuantan Singingi - Wulandari, Indah; Yusuf, Yusmar (CV. Rayyan Dwi Bharata, 2025)
Most of the farmers in Geringging Jaya Village are rubber farmers and are classified as the lower middle class. There are several inhibiting factors such as: weather conditions, pests and diseases, as well as fluctuations in rubber prices received by farmers are relatively low. The purpose of this study is to find out the survival strategies applied by rubber farmers in Geringging Jaya Village, Sentajo Raya District, Kuantan Singingi Regency. This study uses a qualitative method by determining the research subjects as many as 5 (five) people with the technique of determining the subject deliberately (purposive) and (snowball). The data used are primary data and secondary data collected through interviews, observations, and documentation. The results of the research that have been carried out show that rubber farmers in Geringging Jaya Village apply three survival strategies, namely: active strategies, passive strategies, and network-based strategies. The active strategy carried out by rubber farmers is to find a side job, encourage family members to participate in work, and utilize existing resources such as planting plants that are worth selling in the yard. The passive strategy used by rubber farmers is to adopt a culture of frugality. Meanwhile, the network-based strategy applied by rubber farmers, namely: borrowing money from relatives and toke, debting to stall owners, if they need a large amount of money they will borrow from BUMDesa and mobile cooperatives.